Analysis of the Effectiveness of Instagram Marketing on Increasing Customer Interaction at PT Wings Group Surabaya - Riska Widya Sari; Aprilia Mariyam; Riska Kartika Suci; Indah Respati; Rusdi Hidayat (International Journal of Economics Accounting and Management, 2025)
This study evaluated PT Wings Group Surabaya's Instagram marketing strategy to increase customer engagement. Using a quantitative approach through a questionnaire filled out by 100 respondents, this study evaluates the impact of content dimensions, consistency in posts, and the use of Instagram features. The results showed that interactive elements such as Reels, Stories, and Live had the most significant impact on customer engagement, followed by consistency in posting and content variety. The study suggests optimizing Instagram features, improving content quality, and consistency in posts to increase customer engagement and loyalty, while strengthening the company's competitiveness in the digital era.